Association of Serum Vitamin D level with in-hospital Outcome in Patients with Acute Myocardial infarction (Bangladesh Heart Journal, 2022)
Objective: Vitamin D deficiency is emerging as a new risk factor for various cardiovascular events. Several studies have been done to find out association of vitamin D level with CAD with varying Results. Very few studies, however, have investigated the association between serum vitamin D levels and clinical outcomes in ACS patients thus far. The  Objective of this study was to assess the association between serum vitamin D levels and in-hospital complications of AMI patients in Department of Cardiology, Dhaka Medical College Hospital (DMCH), Dhaka.Methods: This was a cross-sectional observational study. We measured serum vitamin D level in AMI (STEMI and NSTEMI) patients (n=198) admitted in Department of Cardiology, DMCH. Patients with normal vitamin D level (e”30 ng/ml) were considered as Group I and patients with low serum vitamin D level (